Dramatic expression in Rameau's Tragédie en musique : between tradition and enlightenment - Verba, Cynthia (Cambridge University Press, 2013)
Verba's fresh approach to understanding Rameau's role in the French Enlightenment focuses on dramatic expression in his musical tragedies.